Solid waste management of the Municipality of Miagao, Iloilo - Negrido, Rosalie M.
With the tons and tons of solid wastes generated everyday around the world, it is necessary to know the effort of the Municipality of Miagao, Iloilo in eliminating the soled wastes it produces in the locality. The research was also conducted in support to the Republic Act (RA) 1760 and 9003. The primary and secondary data gathered through interviews and questionnaires were treated with the use of descriptive-analytical approach. The study aimed to: 1)find out if the Municipality of Miagao has an existing solid Waste Management Program (SWMP); 2) to identify existing solid waste management mechanisms and strategies adopted by the municipality; 3) to determine the level of financial support of the municipality in the implementation of the program; 4) to find out different problems encountered by the municipality in the process of the implementation of the program; and 5) to provide recommendations for the proper solid waste disposal. The Municipality of Miagao has implemented a SWMP. Generally the respondents from both coastal and upland barangays were aware of the program being implemented. Segregation at source is the major strategy used in disposing the solid wastes generated by the household. However, composting and recycling were also encouraged. Poster or slogans were designed to encourage and remind the residents to clean their respective surroundings. Majority of the respondents in both coastal and upland barangays believed that they were involved in the implementation of the said program by abiding the rules and regulations. The local government paid the solid waste collections in the poblacion from the annual budget of the municipality or from the IRA. The garbage collection was collection scheduled twice every week in the town proper. Non Biogradable (or di nabubulok) was collected in the morning while the biogradable (or nabubulok) in the afternoon. Majority of the residents dumps their garbage in the municipal temporary dumpsite through the collection of the municipal garbage collectors in Barangay Kirayan Tacas. The municipal government shoulders the implementation of the SWMP. A moderate level of support of Two Hundred Thousand Pesos (P200,000) for the whole year were allocated by the municipality for the implementation of the SWMP. Poor practice, non-cooperation, irregular solid waste collection and unawareness of the program were the problems encountered by the local government in the process of implementation of the said program as identified by the respondents. A a step forwards a highly efficient SWMP, the following were the recommendations: 1)intensify public awareness through massive information campaign; 2) increase capability building for the key players of the program; 3) increase financial support for the program; 4) strict implementation of the local policies; 5) proper monitoring and continuous evaluation of the program; and 6) continuous effort for research and development.